Regulated breathing modes in pre-season shooting practices of skilled biathletes - Farbey, V. V.; Zhevlakov, E. G.; Klimushin, K. G.; Kurochkin, M. V. (Theory and Practice of Physical Culture, 2018)
The study gives theoretical grounds for application of regulated breathing modes in the skilled biathletes` shooting practices to improve the shooting skills with account of the individual competitive predispositions. Subject to the shooting practices testing experiment were 26 skilled biathletes including 8 shooters, 9 racers and 9 all-round biathletes. The athletes were trained as required by the experimental training model with application of the following breathing control practices: resting practices; breath-holding; forced breathing; zeroing-in breathing; high-rifle-support; mirror-assisted zeroing-in; and close-up (relaxation) breathing practices. The breathing practices were tested in the following Experimental Groups (EG): all-round EG, shooting EG and racing EG, in the varied-intensity training conditions; with the Reference Group trained as required the traditional training model. The breathing control model testing experiment showed its benefits as verified by the EG progress in the varied-intensity training conditions; and found the most efficient regulated breathing modes applicable in different competitive conditions.